Edward Scissorhands [videorecording (DVD)] - Depp, Johnny; Wiest, Dianne; Ryder, Winona, 1971- (20th Century Fox Home Entertainment, 2005)
Once upon a time in a castle high on a hill lived an inventor whose greatest creation was, Edward. Although Edward had an irresistible charm, he was not quite perfect. The inventor's sudden death left him unfinished, with sharp shears of metal for hands. Edward lived alone in the darkness until one day a kind Avon sales person took him home to live with her family. And so began Edward's fantastical adventures in a pastel paradise known as Suburbia.